The Terms Of Language Cavity Morpheme Structure - I Nyoman Suparsa (International Journal of Advanced Science and Technology, 2020)
This study aims to explain the realism of the language cavity morpheme segment, at the phonological level and phonetic level. This study uses linguistic methods and literary methods in data collection. This research was conducted in the city of Komba which included one village and three villages, namely Tanah Rata village, Watu Nggene village, Bamo village, Komba village in East Manggarai regency on Flores island, East Nusa Tenggara Province. The compression includes loud and weak syllable. The compression placement on Rongga language can be explained as bellow. The first, monosyllabic words, wether or not preceded by a consonant or the first syllable of disyllabic words, wether or not preceded by a consonant becomes pressurized (s΄) on a single syllable, wether or not preceded by a consonant or before the second syllable, both of which preceded the consonant or not followed by a word boundary. Second, for three monosyllabic word and four monosyllabic vowel ([+syll]) to be pressurized ([+stress]) (s΄) on the last syllable, both of which preceded the consonant ([-syll]) or not. The results of this study are very useful for speakers of the language itself. During this time, they have never seen and read research on language cavities, especially in the phonological aspects. The results are expected to be considered as one of the considerations for determining the spelling system of the Cavity language, especially the need to define the orthographic determination of consonants and vowels unique in the Cavity language.